Dynamic lecturing : research-based strategies to enhance lecture effectiveness - Harrington, Christine, 1971-; Zakrajsek, Todd (Excellent teacher series., 2017)
Is the lecture an outmoded teaching method that inhibits active learning or is it a potentially powerful tool that is an essential part of every teacher's repertoire? This book presents up-to-date research on the different types of lecture, on what constitutes effective lecturing, and on the impact of lecturing when done appropriately and well. It fills the void in professional development resources on how to lecture, validating the practice when it's aligned with the educational mission of creating engaged learning environments. Christine Harrington and Todd Zakrajsek demonstrate that, rather than lecture and active learning being mutually exclusive or either-or propositions, the effectiveness of the former can be greatly enhanced when combined with active learning techniques through what they define as dynamic lecturing; and provide context about the need to balance these approaches to meet the needs of students as they progress from novice to advanced learners. They present a range of strategies that enhance student learning during lectures. They open each chapter with the evidence behind each lecturing strategy they describe, and conclude with practical suggestions for quick application in the classroom. They offer readers the lecture planning and evaluation tools for reworking their lectures in ways that provide high-level engagement and achievement for their students. The opening section of the book explores the benefits of lecturing and describes the different modalities of lecture, with an assessment of the advantages and disadvantages of each. The second section focuses on educational strategies to enhance the lecture, including, among others, activating prior knowledge, emphasizing important points, effectively using multi-media, making concepts meaningful via examples, and the importance of retrieval practice. Each covers the underlying theory and research, and advice on how to align the engagement techniques with instructional goals. The book concludes with guidance on effective planning for lecturing and helping chairs, administrators, or peers engage in effective evaluation of the lecture. This is a dynamic resource for all faculty interested in revitalizing their teaching. The strategies are succinct, easy to incorporate into lectures and, done well, will have immediate impact and increase student mastery of course content.--Provided by publisher.